1985
DOI: 10.1007/bf00269373
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis and plant regeneration from cultured endosperm of Emblica officinalis Gaertn

Abstract: Mature endosperm of Emblica Officinalis (Euphorbiaceae) formed a continously growing callus on MS medium supplemented with an auxin (2,4-D or IAA) and a cytokinin (K or BAP). Subculture of callus on MS with BAP (0.2 mg/l) and IAA (0.1 mg/l) resulted in formation of shoots and embryo-like structures in 50 and 8 per cent cultures, respectively. Regeneration of shoots was more frequent when both BAP (0.2 mg/l) and IAA (0.1 mg/l) were present than on BAP (0.2 mg/l) alone. The embryo-like structures produced plantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…It is reported that during germination the embryo releases certain gibberellin like substances, which may promote the endosperm proliferation (Ogawa 1964;Ingale and Hageman 1965). However, the mature endosperms of Achras sapota (Bapat and Narayanaswamy 1977), Santalum album (Lakshmi Sita et al 1980), Emblica officinalis (Sehgal and Khurana 1985) and Juglans regia (Cheema and Mehra 1982;Tulecke et al 1988) could proliferate without the association of embryo or pre-soaking of them in GA 3 .…”
Section: The Embryo Factormentioning
confidence: 94%
See 2 more Smart Citations
“…It is reported that during germination the embryo releases certain gibberellin like substances, which may promote the endosperm proliferation (Ogawa 1964;Ingale and Hageman 1965). However, the mature endosperms of Achras sapota (Bapat and Narayanaswamy 1977), Santalum album (Lakshmi Sita et al 1980), Emblica officinalis (Sehgal and Khurana 1985) and Juglans regia (Cheema and Mehra 1982;Tulecke et al 1988) could proliferate without the association of embryo or pre-soaking of them in GA 3 .…”
Section: The Embryo Factormentioning
confidence: 94%
“…However, on IAA supplemented medium the callus gave rise to shoots in 100% cultures (Nag and Johri 1971). Sehgal and Khurana (1985) 45.…”
Section: Ricinus Communismentioning
confidence: 97%
See 1 more Smart Citation
“…The addition of an auxin induces callus in the endosperm of Euphorbia [27] and Nigella [28]. Annona [29], Emblica [30],Juglans [9] and Lycium [31] require both an auxin and cytokinin, and for Prunus, [33] …”
Section: Immature Endospermmentioning
confidence: 99%
“…In vitro morphogenesis has been accomplished in many forest tree species [1,4,13,14]. Various species of Populus have been studied extensively for plant regeneration from protoplasts [12], callus [10], axillary buds [11], stem internodes [5,6] and immature embryo explant [8].…”
Section: Introductionmentioning
confidence: 99%